Thoracic Outlet Syndrome: Fingertip Cannot Replace Forearm Photoplethysmography in the Evaluation of Positional Venous Outflow Impairments - Hersant, Jeanne; Ramondou, Pierre; Durand, Sylvain; Feuilloy, Mathieu; Daligault, Mickael; Abraham, Pierre; Henni, Samir (Frontiers in Physiology, 2021)
Objective: Fingertip pulse plethysmography (PPG) resulting from high-pass filtered raw PPG signal is often used to record arterial pulse changes in patients with suspected thoracic outlet syndrome (TOS). Results from venous (low-pass filtered raw signal) forearm PPG (V-PPG), during the candlestick-Prayer (Ca+Pra) maneuver was recently classified into 4 different patterns in patients with suspected TOS, two of which are suggestive of the presence of outflow impairment. We aimed to test the effect of probe position (fingertip versus forearm) and of red (R) versus infrared (IR) light wavelength on V-PPG classification, and compared pattern classifications to the results of ultrasound. Methods: In patients with suspected TOS, we routinely perform ultrasound imaging (US+ being the presence of a positional compression) and Ca+Pra tests with forearm V-PPGIR. We recruited patients for a Ca+Pra maneuver with simultaneous fingertip and forearm V-PPGR. The correlation of each V-PPG recording to each of the published pattern profiles was calculated. Each record was classified according to the patterns for which the coefficient of correlation was the highest. Cohen’s Kappa test was used to determine the reliability of classification between forearm V-PPGIR, fingertip V-PPGR, and forearm V-PPGR. Results: We obtained 40 measurements from 20 patients (40.2 +/-11.3 years old, 11 males). We found 13 limbs with US+ results, while V-PPG suggested the presence of venous outflow impairment in 27 and 20 limbs with forearm V-PPGIR and forearm V-PPGR, respectively. Fingertip V-PPGR provided no patterns suggesting outflow impairment. Conclusion: We found more V-PPG patterns suggesting venous outflow impairment than US+ results. Probe position is essential if aiming to perform upper-limb V-PPG during the Ca+Pra maneuver in patients with suspected TOS. V-PPG during the Ca+Pra maneuver is of low cost, easy, and provides reliable, recordable, and objective evidence of forearm swelling. It should be performed on the forearm (close to the elbow) with either red or infrared PPG, but not at the fingertip level.